Carlsbad Caverns National Park Air Quality Study 2019 - Sullivan, Amy P.; Naimie, Lillian E.; Benedict, K. B.; Prenni, Anthony J.; Sive, B. C.; Fischer, Emily V.; Pollack, Ilana; Collett, Jeffrey; Schichtel, Bret A. (Colorado State University. Libraries, 2022)
Carlsbad Caverns National Park in southeastern New Mexico is adjacent to the Permian Basin, one of the most productive oil and gas regions in the country. The 2019 Carlsbad Caverns Air Quality Study (CarCavAQS) was designed to examine the influence of regional sources, including urban emissions, oil and gas development, wildfires, and soil dust on air quality in the park. Field measurements of aerosols, trace gases, and deposition were conducted from 25 July through 5 September 2019.
This data set includes fine particle and gas precursor measurements from Carlsbad Caverns National Park. The study was designed to examine the influence of regional sources, including urban emissions, oil and gas development, wildfires, and soil dust on air quality in the park. Field measurements of aerosols, trace gases and deposition were conducted from 25 July through 5 September 2019.
Department of Atmospheric Science
This dataset was updated on June 23, 2025 to add two Excel files (CAVE2019_VOCs_GC.xlsx, CAVE2019_VOCs_PTRMS.xlsx) and one documentation file (CAVE2019_VOCs_ReadMe.pdf). The dataset's main ReadMe file (CAVE2019_ReadMe_20250623.pdf) was updated to reflect these additions.
Keywords: National Parks; PM2.5; Visibility; Carlsbad Caverns